2017
DOI: 10.5688/ajpe5956
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of California Pharmacy and Medical Students’ Dietary and Lifestyle Practices

Abstract: Objective. To assess dietary and lifestyle practices of pharmacy and medical students in California and investigate whether they adhered to behaviors consistent with current dietary and exercise guidelines. Methods. The Block Brief 2000 Food Frequency Questionnaire and a supplemental survey assessing demographics, exercise, and dietary behaviors were administered to students across 10 California pharmacy and medical schools. Results. While the majority of students consumed sodium ,2300 mg/day (73%) and dietary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
19
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 39 publications
7
19
0
1
Order By: Relevance
“…In vegetables, we found that the consumptions of green leafy vegetables on daily basis were higher in Chinese students as compare to international students. Fast food, a high energy-dense diet, low in fiber, and poor in micronutrients, associated with unhealthy weight gain and obesity [ 36 ]. In our study, most students consumed fast food on weekly basis, but this percentage was found more in international students.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In vegetables, we found that the consumptions of green leafy vegetables on daily basis were higher in Chinese students as compare to international students. Fast food, a high energy-dense diet, low in fiber, and poor in micronutrients, associated with unhealthy weight gain and obesity [ 36 ]. In our study, most students consumed fast food on weekly basis, but this percentage was found more in international students.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, most students consumed fast food on weekly basis, but this percentage was found more in international students. A study in medical students showed that 60% of the medical students consume fast food from weekly basis to monthly basis [ 36 ]. Another study reported that in US adults 57% of 18–29 years eat fast food on weekly basis and 33% eat on monthly basis [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…A lower score indicates a more healthful diet (minimum = 0, maximum = 16) [ 27 ]. The STC questionnaire has successfully been used to identify changes in dietary patterns over a four-month period [ 27 ] (including with college students [ 28 , 29 ]), making it a useful measure of dietary behaviors in this timeframe and population. The Alcohol Use Disorders Identification Test-Consumption (AUDIT-C) was used to screen participants for heavy drinking or alcohol abuse [ 30 ].…”
Section: Methodsmentioning
confidence: 99%
“…4 ,3 It has been found that these unhealthy behaviors are also common and worrying among university students. [5][6][7] This age period is very critical due to development of life style habits which may affect the progression of common NCDs. [8][9][10] At this period, the likelihood of fast food consumption is higher than healthy foods and on the other hand, due to time constraints, physical activity also reduced.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10] At this period, the likelihood of fast food consumption is higher than healthy foods and on the other hand, due to time constraints, physical activity also reduced. 7 Therefore, the universities have great opportunity to establish healthy behavioral choices among their students through effective health promoting interventions . 9 To improve healthy behaviors among young adult, the first step is to measure their lifestyle by a valid and reliable tool.…”
Section: Introductionmentioning
confidence: 99%